2001
DOI: 10.1111/j.1469-7793.2001.0301i.x
|View full text |Cite
|
Sign up to set email alerts
|

Location of the initiation site of calcium transients and sparks in rabbit heart Purkinje cells

Abstract: 2+ ] i (calcium sparks) have been identified in cardiac, smooth and skeletal muscle (reviewed by Cheng et al. 1996b). A number of authors have suggested that Ca 2+ transients are due the spatio-temporal summation of many Ca 2+ sparks Cheng et al. 1995;Tanaka et al. 1998). These Ca 2+ sparks are the result of release of Ca 2+ from the SR and are believed to be the elementary events underlying E-C coupling in cardiac muscle (Cheng et al. 1993;Bridge et al. 1999). Shacklock et al. (1995) have shown that location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
103
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 33 publications
16
103
2
Order By: Relevance
“…4). Similar to normal rabbit Purkinje cells with isoproterenol, 20 we found that in IZPCs (in the absence of isoproterenol), a cellwide wave is preceded by highly frequent μCaiTs (Fig. 1).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…4). Similar to normal rabbit Purkinje cells with isoproterenol, 20 we found that in IZPCs (in the absence of isoproterenol), a cellwide wave is preceded by highly frequent μCaiTs (Fig. 1).…”
Section: Discussionsupporting
confidence: 70%
“…13 It also can restore coordination of Ca 2+ sparks in myocytes from an infarcted heart. 14 Others have suggested that isoproterenol has no effect on spark frequency or distribution, that it can or cannot increase spark amplitude but can accelerate its decay and increase the maximal rate of release 15 , 16 (but see references 17 -19 20 It is widely accepted that isoproterenol increases the rate of firing of canine Purkinje fibers. In this study, we report that isoproterenol increased both μCaiT and cell-wide Ca 2+ waves in normal Purkinje cell aggregates, consistent with observations that isoproterenol enhances membrane depolarization and the amplitude of delayed afterdepolarizations in normal canine Purkinje fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Individual RyR cluster size can vary over a continuous distribution (from <10 up to 250 RyRs), but some smaller clusters are quite close to others (eg, at the same junction) and, because of their proximity (within 100 nm), may function as a single junctional cluster. This proximity explains how a small local Ca 2+ influx can activate multiple RyRs via Ca 2+ ‐induced Ca 2+ ‐release (CICR) during the normal action potential–induced Ca 2+ transient and also during diastolic Ca 2+ sparks 7, 8, 9, 10, 11. Ca 2+ sparks are stochastic local CICR events that are typically restricted spatially to 1 cluster/junction without propagation to nearest‐neighbor junctions spaced 1.8 to 1.9 μm longitudinally or 0.4 to 0.8 μm transversely 8, 9, 10, 11, 12.…”
mentioning
confidence: 98%
“…Most (82%) of these events (amplitudeϭ1.85Ϯ0.02 F/Fo; duration at half maximal amplitude [T 0.5 ]ϭ41Ϯ1 ms; full width at half maximal amplitude [FWHM]ϭ3.2Ϯ0.1 m; rateϭ0.6Ϯ0.2 events per s per 100 m; nϭ524) were similar to Ca 2ϩ sparks reported for rabbit Pcells. 6,15 The remaining nonpropagating Ca 2ϩ transients had amplitude above 3 F/Fo (amplitudeϭ4.9Ϯ0.2 F/Fo; T 0.5 ϭ43Ϯ2 ms; FWHM: 2.4Ϯ0.2 m; rateϭ0.13Ϯ0.04 events per s per 100 m scan; nϭ115; Figure 1A). Clusters of consecutive and/or simultaneous Ca 2ϩ sparks ( Figure 1B) were also detected predominantly in regions below the sarcolemma and were similar to compound sparks described previously.…”
Section: Nonpropagating Ca 2؉ Transientsmentioning
confidence: 99%